“Dancing with Preschoolers Makes My Day”: A Male Educator’s Perspective on His Profession - Anti Wulan Nurcahaya; Hani Yulindrasari; Tina Hayati Dahlan (SEAMEO CECCEP, 2023)
Internationally, the profession of preschool educators is more dominated by females than males. Male educators in early childhood education (ECE) are very rare, however, the presence of male and female educators in ECE will be very meaningful in the balance of gender construction in early childhood. This study aims to explore the perceptions of a male teacher at ECE regarding his profession as an ECE teacher as well as a dance teacher. This research used a narrative qualitative approach, conducted in a kindergarten in Bandung that has a male teacher who also teaches dancing extracurriculars. Through the experiences and chronology of the teacher's career journey, the researcher tried to understand the reasons and factors that make the teacher in love and comfortable with his current profession, despite the fact about gender stereotypes in society. The teacher even preferred to continue his career at ECE even though he had been accepted by PPPK (Government Employee with Employment Agreement) at another educational unit (Junior High School). The results of this study indicate that from the male teacher's perspective: (1) working in an ECE environment with preschoolers is more dynamic that encourages creativity, (2) in line with his passion which increases his work engagement and well-being, and (3) there are opportunities for his self-development. Experiences and a supportive environment made a male teacher finally found his passion and chose to work at ECE.